FENOMENA NON FARM - Malik, Nazaruddin (Jurnal Bestari, 1994)
There is a tendency that the area of land for agriculture gets narrower and narrower and the rate of rural population growth increases the number of unemployment in countries. Meanwhile the development strategies applied in the sector of agriculture seems uncapable of giving opportunity for the growth of new job alternatives in the sector of nonagriculture. Therefore, what is needed at this time is that agricultural sector considering the interrelatedness between the sector of agriculture and non-agriculture.